ANALISIS STABILITAS LERENG MODIFIKASI- STABILISASI TANAH DENGAN PENAMBAHAN KAPUR (Studi Kasus Area Kantor Pemda Seluma) - mawardi, mawardi (Universitas Bengkulu, 2022)
ABSTRACTSeluma regency area often occurs landslide disaster and one of them is located in Local Government Authority Seluma area. This study aims to analyze the stability of the slope by using finite element method, so it is known that the safety factor (SF) and the soil type. The study was started by testing physical and mechanical properties of the soil, then slope stability analysis was done by finite element method program to find out FK. The result of soil physical properties test shows that the land on the slope of Local Government Authority Seluma area is clay soil. Calculation of slope stability analysis using finite element method by considering the effect of pore water to get the safest result on slope cement stabilization soil 1 Contour A, SF= 1,817 with a slope angle of 34o. The slopes studied in the Local Government Authority in Seluma Regency are all prone to landslides or unsafe because SF is < 1,5. Based on the results of the research from the safest slope, it was concluded that the value of the Safety Factor (SF) of soil stabilization of limestone was 1,817 bigger than the value of the safety Factor (SF) of soil compaction was 1,619 and the value of the safety Factor (SF) of soil compaction was 1,399 bigger than the value of the safety Factor (SF) of the original soil was 1,483.Key Words : Finite Element Method, Safety Factor, Modifications slope, Slope StabilityABSTRAKAreal Kabupaten Seluma sering terjadi peristiwa longsor dan salah satunya berada di kawasan Kantor Pemda Seluma. Penelitian ini bertujuan untuk menganalisis stabilitas lereng dengan menggunakan metode finite element, sehingga diketahui faktor keamanan (FK) dan jenis tanah. Penelitian dimulai dengan melakukan uji sifat fisis dan mekanik tanah, kemudian dilakukan analaisis stabilitas lereng dengan metode finite element untuk mengetahui FK. Hasil pengujian sifat fisis tanah menunjukan bahwa tanah pada lereng dikawasan Kantor Pemda Seluma adalah tanah lempung. Perhitungan analisis stabilitas lereng menggunakan metode finite element dengan mempertimbangkan pengaruh air pori mendapatkan hasil yang paling aman pada tanah stabilisasi Kapur lereng 1 Kontur A, FK= 1,817 dengan kemiringan sudut lereng 34o. Lereng yang diteliti di kawasan Kantor Pemda Seluma semuanya rawan longsor atau tidak aman karena FK < 1,5. Berdasarkan hasil penelitian dari lereng yang paling aman disimpulkan bahwa nilai Faktor Keamanan (FK) tanah stabilisasi Kapur adalah 1,817 lebih besar dari nilai Faktor Keamanan (FK) Tanah pemadatan adalah 1,619 dan nilai Faktor Keamanan (FK) tanah pemadatan adalah 1,619 lebih besar dari nilai Faktor Keamanan (FK) tanah asli adalah 1,483Kata Kunci : Metode Finite Element, Faktor Aman, lereng modifikasi, Stabilitas Lereng